2009
DOI: 10.1042/cs20080561
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis acutely reduces the plasma levels of ADMA without reversing impaired NO-dependent vasodilation

Abstract: End-stage renal disease patients have endothelial dysfunction and high plasma levels of ADMA (asymmetric omega-NG,NG-dimethylarginine), an endogenous inhibitor of NOS (NO synthase). The actual link between these abnormalities is controversial. Therefore, in the present study, we investigated whether HD (haemodialysis) has an acute impact on NO-dependent vasodilation and plasma ADMA in these patients. A total of 24 patients undergoing maintenance HD (HD group) and 24 age- and gender-matched healthy controls (Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
3
12
1
1
Order By: Relevance
“…17 However, more recent clinical studies have shown a significant decrease in blood levels of ADMA. 18,19 One explanation for the conflicting results may be the result of the protein binding of ADMA, 20 however, even the extracorporeal liver support system Prometheus TM (Fresenius Medical Care, Germany), which allows the removal of protein-bound toxins, decreased ADMA by only 25%, 21 further highlighting the metabolic pathways for controlling ADMA levels.…”
Section: Origin and Removal Of Adma And Sdmamentioning
confidence: 93%
“…17 However, more recent clinical studies have shown a significant decrease in blood levels of ADMA. 18,19 One explanation for the conflicting results may be the result of the protein binding of ADMA, 20 however, even the extracorporeal liver support system Prometheus TM (Fresenius Medical Care, Germany), which allows the removal of protein-bound toxins, decreased ADMA by only 25%, 21 further highlighting the metabolic pathways for controlling ADMA levels.…”
Section: Origin and Removal Of Adma And Sdmamentioning
confidence: 93%
“…Even if these findings are in agreement with previous observations [52,56,[95][96][97], the mechanisms of these alterations and their possible relationship have not been fully elucidated.…”
Section: Microvascular Reactivity In Lean Overweight and Obese Hypersupporting
confidence: 81%
“…The within-subject variabilities determined at fixed skin sites of healthy young subjects were 15-25% for both iontophoretic and local thermal provocations in our laboratory. In order to validate the modified LDF protocol in the clinical setting, the microvascular reactivities of 12 HD patients were assessed as the presence of an impaired microvascular function had previously been demonstrated in this group [95][96][97]. In agreement with the literature, the endothelium-dependent and -independent vasodilation both proved to be markedly diminished as compared with those in healthy young subjects (p<0.001 vs the controls; data not published) ( Table 1).…”
Section: Validation Of the Laser Doppler Flowmetry Protocolsupporting
confidence: 68%
See 1 more Smart Citation
“…Згідно з даними Meyer і співавт. [85], один сеанс ГД погіршував ендотелійзалежну ва-зодилатацію; в інших працях -остання не змінювалась [86] або покращувалась [87]. Вміст стабільних метаболітів NO після сеан-су ГД змінювався [88][89][90], а дослідження, прис вячені вивченню динаміки циркулюю чих ендотеліальних клітин як морфологічного маркера пошкодження ендотелію протягом ГД, поодинокі [91].…”
Section: сучасні тенденції розвитку науки індуктори та інгібітори каunclassified